Some Observations on Bursera penicillata (DC.) Engl. (B. delpechiana Poiss ex Engl.) - Hussain, A. M. Mahmood; Subramanian, K. N.; Madhavan Nair, J. (Indian Forester, 1974)
Some observations are made on the morphological characters, pollen viability and effect of artificial pollination of Bursera penicillata an essential oil yielding species. Artificial pollination using fresh pollen grains is suggested to improve fruit setting in this species.